(PM-355)دراسة متغيرات القشط الكيمياوي لكاشف الااثار النوويه - عجيل, كاظم (University of Thi-Qar Journal of Science, 2010)
We study in this research the ectching characteristics of nuclear track polymeric detecter (PM-355) which was one from (CR-39) detecter group ,known as”super”, by using the chemical etching method with NaOH and KOH solution in normality rang (412N) at (50-70)C 0 as etching temperature , after irradiating the samples with (5.4MeV) alpha particles from(Am 241 )source. We found following results:the bulk ,track and diameter etching rates(V B, V T,V increased with increasing the normality and etching temperature. These parameters became greater when KOH solution wasused .Also we determined the etch induction time values ,where we found it dristically decreased as highly as normality . The etch rate ratio (v) valuses were determind at this alpha energy as well as at (4, 2.5 MeV )at (70 C D) 0 )and at (6N) (NaOH) at(50-60C 0 )then we conclud that the (6N) NaOH at (70C 0 ) was the optimum etching condition for (PM- 355) detector. The etch induction time was specified at the optimum etching condition by using the opticel density from foil which gives a result differ from the normal method.